The Teaching Profession in Mexico: a Job in Process of Reconfiguration - Jesús Francisco Galaz Fontes; Manuel Gil Antón (Universidad Autónoma de Baja California, 2009)
This work is part of the international research project, The Changing Academic Profession (CAP), which is studying the reconfiguration of the teaching profession in more than 20 countries. It explores the specific ways in which the process of academic work has been transformed in Mexico. The features of this professional activity, as centered in the academic world of the institutions of higher education at the beginning of the 1990's?when compared with its present characteristics?throw light, pose questions and make conjectures about this significant change, as well as about lines of continuity that must be recognized and explained. The reconfiguration of the academic profession in Mexico has occurred in the context of a public-policy agenda concerning higher education and academic personnel. We approach this question for the purpose of locating its analysis in the context of a new regulatory framework of academic life. This new effort is part of the series of studies carried out in the country during the last twenty years, and gives evidence for the teaching profession's reconfiguration in four dimensions: gender; teacher's age on entering the profession; composition of the faculty according to academic level; level of scholarity of academics' families of origin, and families today. It also explores the variations that have occurred during the fifteen years in which the new policies have been in operation in different types of institutions, since the academic world as a whole is made up of small and diverse subworlds. This article ends with a general reflection on these changes. Key words: Faculty, higher education, academic profession.